Relative Bioavailability Study of a New Medium/Long-chain Triglyceride Emulsion of Propofol in Beagle Dogs - Chen, W.; Cai, Y.-Q. (Drug Research, 2013)
The aim of this study was to evaluate the bioequivalence of a new generic formulation of propofol medium/long-chain triglyceride emulsion (test) and the available branded formulation (reference) to comply with regulatory criteria for marketing of the test product in China. This single-dose, randomized-sequence, open-label, 2-period crossover study was conducted in 6 beagle dogs. Blood samples were collected before dosing and at different time after dosing. Plasma samples were separated and assayed for propofol using a selective and sensitive HPLC method with fluorescence detection. The pharmacokinetic parameters AUC0-T, AUC0-∞, MRT, t1/2 and CL were determined from plasma concentration-time profile of both formulations. The formulations were considered bioequivalent when the 90% CIs of the geometric mean ratios (test:reference) for AUC0-T and AUC0-∞ were within the regulatory range of 80% to 125%.
Keywords: propofol; HPLC; fluorescence detection; pharmacokinetic parameters